The prevalence and factors associated with obesity among adult women in Selangor, Malaysia. - Mohd Sidik, Sherina; Gyanchand Rampal, Lekhraj Rampal (BioMed Central, 2009)
Introduction: The prevalence of obesity in developing countries especially among women is on the rise. This matter should be taken seriously because it can burden the health care systems and lower the quality of life.